Metode Pembelajaran Sistem Pakar Diagnosa Penyakit Ikan Hias Air Tawar Pada SMK Negeri 2 Tangerang - Herowati Herowati; Agung Pambudi; Nurbayti Nurbayti (UNIVERSITAS RAHARJA, 2017)
The year 1830, munculah called zoetrope, cylindrical object with empty spaces with pictures drawn by hand on the surface of it. While playing, the same motion effect. The year 1870, an inventor from France, Emile Reynaud added a mirror in the middle of the cylinder space. A few years later, he discovered the version of Windows will arise. By adding light reflector and lenses to magnify images on the screen. The year 1892, he did a demonstration in Paris's Theatre Optique, with hundreds of images using the hands to cause the effect of motion pictures for 15 minutes. Rouben Mamoulian, an American film director born in 1929 demonstrated various types of sound in a movie. This is then pushed the filmmaker makes the soft-spoken. The first film camera that uses a color separation. Technicolor Camera that was discovered in 1932 using the principle of